The influence of various sample storage conditions and sample microbial contamination on concentrations of routine biochemical parameters - Gojkovic, Tamara; Vladimirov, Sandra; Antonic, Tamara; Bogavac-Stanojevic, Natasa; Novovic, Katarina; Spasojevic-Kalimanovska, Vesna; Filipic, Brankica (Journal of Medical Biochemistry, 2023)
Background: The pre-analytical (PA) phase is the most vulnerable phase of laboratory testing procedure, with critical procedures-collection, handling, sample transport, and time and temperature of sample storage. The aim of this study was to examine if different anticoagulants, storage conditions, and freeze-thaw cycles (FTCs) influence the concentrations of basic biochemical parameters. In parallel, the presence and the effect of sample microbiological contamination during routine laboratory work were examined. Methods: Two plasma pools (EDTA, and sodium-fluoride/potassium oxalate plasma (NaF)) were stored at +4C˚/-20˚C. Total cholesterol (TC), glucose, triglycerides (TG), urea, total protein (TP), and albumin concentrations were measured using Ilab 300+. Sample microbiological contamination was determined by 16S rRNA sequence analysis. The experiment encompassed a 5 day-period: Day 1–fresh sample, Day 2–1st FTC, Day 3–2nd FTC, Day 4–3rd FTC, Day 5–4th FTC. The appearance of bacteria in two consecutive samples was the experiment’s endpoint. Results: During 4 FTCs there were no changes in plasma urea concentrations. Glucose was stable in EDTA+4˚C and NaF- 20˚C until the 3rd FTC (P=0.008, P=0.042, respectively). Changes in protein concentrations followed the zig-zag pattern. TG concentrations changed significantly in the EDTA-20˚C sample after 1st and 4th FTCs (P=0.022, P=0.010, respectively). In NaF samples no contamination was observed during 4 FTCs. Conclusions: Urea and glucose concentrations were robust. Changes in lipid and protein concentrations after FTCs follow complex patterns. Bacterial growth was not observed in NaF plasma samples. This can promote NaF use in analytical procedures in which microbiological contamination affects the quality of analysis.